The level of IgG antibodies reactive to TF, Tn and Alpha-Gal polyacrylamide-glycoconjugates in breast cancer patients: relation to survival - Smorodin, E.P.; Sergeyev, B.L. (Experimental Oncology, 2016)
Background: The serum levels of IgG antibodies reactive to glycoconjugates (TF, Tn and αGal) were found to be associated with prognosis of gastrointestinal cancer patients. Aim: To study the relation between the levels of serum antibodies to TF-pAA, Tn-PAA and αGal-PAA polyacrylamide-based glycoconjugates and survival in breast cancer. Materials and Methods: The preoperative level of IgG antibodies was analysed in the serum of patients (n = 59) using ELISA with polyacrylamide-glycoconjugates namely, TF-pAA (amide-type), and ethanolamide-conjugates Tn-PAA and αGal-PAA. Survival rate and hazard ratio (HR) were assessed by the Kaplan — Meier method and Cox univariate analysis in different pathomorphological groups. Results: Significantly better survival was observed in patients with an increased level of anti-TF-pAA antibodies both for all patients in total and groups in stages II–III; N1–2 and G3 (p = 0.008–0.021, HR = 0.18–0.23, mean survival time in months 164–186 vs 69–121). A trend to worse survival was observed in increased level of anti-Tn IgG (stages II–III) and anti-αGal IgG (G3): p = 0.075, HR = 2.49 and p = 0.066, HR = 3.27, respectively. Conclusion: The method for the determination of circulating anti-TF-pAA IgG may be a useful supplement in long-term prognostic assessment of patients with breast cancer.